INMATE TRANSFORMATION AND VOCATIONAL CAPITAL IN CENTRAL LOMBOK OPEN PRISON, INDONESIA - Ahmad Surya Negara; Muhammad Aziz (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2026)
This study analyzes inmate rehabilitation in the Class IIB Lombok Tengah Open Prison using the architecture of freedom concept. Employing a qualitative case study with Desistance and Human Capital theories, data were gathered through observation and interviews. Findings reveal that the minimum-security environment facilitates identity transformation from offenders to pro-social individuals by providing leadership roles in religious activities. Furthermore, agricultural programs significantly build human capital through technical skill mastery, despite structural barriers like limited infrastructure. The study concludes that synergy between psychological readiness and economic empowerment is vital for successful social reintegration and recidivism prevention. These results recommend modernizing vocational facilities and strengthening post-release support to optimize Indonesia's open prison model.